An overview of carbapenem-resistant organisms from food-producing animals, seafood, aquaculture, companion animals, and wildlife - Ramírez-Castillo, Flor Y.; Guerrero-Barrera, Alma L.; Avelar-González, Francisco J. (Frontiers in Veterinary Science, 2023)
Carbapenem-resistant (CR) is a major health problem worldwide. In clinical settings, CR is a growing challenge due to rapid dissemination and low treatment option, however characterization of the molecular mechanisms and epidemiology is highly study. Regarding spread of CR in food-producing animals as well as in the environment and the health risk that represent to human, little is known. In this mini-review, we pointed to discuss the detection of carbapenem-resistance organisms and their mechanisms in pigs, cattle, poultry, aquatic food-producing animals and wildlife. We also pointed out the One Health approach as a strategy to attempted the emergency and dispersion of carbapenem-resistance in this sector as well as to determine the role of carbapenem-producing bacteria in animals among human public health risk. We observed a higher occurrence among carbapenem-enzymes in livestock on poultry and swine. Carbapenem-resistance in cattle is still rare. Studies related to poultry highlight to P. mirabilis, E. coli and K. pneumoniae as NDM-5 and NDM-1-producing leading the resistance to carbapenems. Among cattle, OXA and NDM-producing bacteria are the higher reported, mainly by E. coli and A. baumanii. On swine, OXA-181, IMP-27 and VIM-1 genes were also detected. Among wildlife and companion animals, high prevalence of carbapenem-enzymes has been reported suggesting the role on the transmission of carbapenems-resistant genes. The presence of antibiotic resistant organisms in aquatic environment should be taken account since might act as a reservoir for carbapenem resistant genes and their dissemination through all the ecosystems. It is urgent to implement the One Health approach worldwide in order to made all the efforts to contain the dissemination of carbapenem resistance genes.